CORPORATIONS AS WHISTLEBLOWERS IN THE CRIME OF DEFAMATION BASED ON THE ELECTRONIC AND TRANSACTION INFORMATION ACT - Dwikarunia Setiawan Guntik; Dewa Gede Pradnya Yustiawan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
The purpose of writing this article is to find out whether the corporation can be a reporting party in the criminal act of defamation under the ITE Law. The methods performed in writing this article are normative legal research methods that use a type of statutory approach and a conceptual approach. The results of the study showed that the regulation of defamation crimes stipulated in the Criminal Code and ITE Law, corporations cannot be the reporting party in the criminal act of defamation under the ITE Law because based on letter a guidelines for the implementation of Article 27 Paragraph (3) of SkB No. 2/VI/2021 on guidelines for the implementation of the ITE Law stipulate that the understanding of the content of insults and / or defamation must refer to the provisions of Article 310 and 311 of the Criminal Code in addition to letter f The implementation guidelines of Article 27 Paragraph (3) of the ITE Law stipulates that victims who can become whistleblowers are only individuals with a specific identity so that corporations cannot be reporting parties under the ITE Law. Corporations cannot be the reporting party should be included in the article explanation to be binding in an arrangement because the nature of the DECREE containing implementation guidelines is only binding on law enforcement only.